(untitled) (Materiali di Estetica. Terza serie, 2022)
The essay presents the debate between national PCI and Milan’s PCI about the building of a new popular culture after the fall of fascism. The philosopher Antonio Banfi and the writer Elio Vittorini were the protagonists of this period. Banfi had already analysed this issue in the “Fronte della cultura” and in the programmes of the “Casa della Cultura” of Milan, while Vittorini had intervened with some articles published in the Florentine periodical «Il Bargello» then recalled in «Il Politecnico». Their point of view would have been questioned by national PCI in which prevailed the cultural approach inspired by Gramsci’s «Quaderni del carcere» that came out in the same years